Вимоги до раціону харчування військовослужбовців Збройних Сил України - Семко, ‪Тетяна Василівна; Semko, Tetiana; Пахомська, Олена Василівна; Pahomska, Olena (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: В умовах сьогодення дослідження питань забезпечення раціональним та повноцінним харчу-ванням військовослужбовців Збройних Сил України є надзвичайно необхідним і важливим. З огляду на це, особливої актуальності набуває питання розроблення та наукового обґрунтування захо-дів, спрямованих на забезпечення раціонального харчування військовослужбовців необхідними поживними речовинами.Вимоги до раціону харчування військовослужбовців в Україні регламентуються постановою КМ України No 426 «Про норми харчування військовослужбовців Збройних Сил та інших військових формувань» від 29 березня 2002 р. (14 Норм), яку постановою КМ України від 3 жовтня 2016 р. No 696 «Про внесення змін до норм харчування військовослужбовців ЗСУ та інших військових формувань» доповнено Нормою No 15 – добовий польовий набір продуктів. Для забезпечення високого рівня фізичного та емоційного стану військовослужбовців під час виконання службово-бойових завдань необхідно забезпечити повноцінне харчування й налагодити логістику постачан-ня харчових продуктів. /// EN: In today's conditions, the study of the issues of providing rational and complete nutrition to the servicemen of the Armed Forces of Ukraine is extremely necessary and important.Based on this, the issue of development and scientific substantiation of measures aimed at ensuring the rational nutrition of military personnel with all the necessary nutrients becomes especially urgent.The requirements for the diet of military personnel in Ukraine are regulated by Resolution of the Cabinet of Ministers of Ukraine No 426 “On Nutrition Standards of Servicemen of the Armed Forces and Other Military Formations” dated March 29, 2002 (14 Norms), which by Resolution of the Cabinet of Ministers of Ukraine dated October 3, 2016 No 696 “On making changes to the food standards of servicemen of the Armed Forces of Ukraine and other military formations” supplemented by Norm No 15 – daily field set of products.Optimizing the food system of military personnel is achieved through the introduction of various diets, the use of a wide range of products, the development of dry rations intended for food in combat conditions.The improvement of food technology for the military personnel of Ukraine at the current stage of development is taking place in certain directions:– provision and use of high-quality and environmentally friendly raw materials; fast and high-quality primary processing of raw materials and their transportation in a cooled state to the place of processing;– heat treatment of raw materials and mixtures under economical regimes in order to maximize the preservation of dietary components; – design of balanced nutritional composition (content) of combined products;– use of new types of chemically inert and convenient packaging materials;– enrichment of products with natural flavoring and vitamin components;– increase in the shelf life of products due to vacuum packaging and low moisture content in food products;– elimination of the influence of external harmful factors on raw materials during the technological process of its processing and during storage and sale of productsIn order to ensure a high level of physical and emotional state of servicemen during the performance of service and combat tasks, it is necessary to ensure adequate nutrition and to establish the logistics of food supply.
Requirements for the nutrition of military servicemen of the armed forces of Ukraine
Keywords: раціональне харчування; каталог продуктів; збалансованість; військовослужбовці; харчовий раціон; фізіологічна норма; rational nutrition; product catalog; balance; military personnel; food ration; physiological norm